Experimental study of distribution and quantitative characterization of discontinuous oil phase based on micro-CT - Yang, Jiangshan; Shan, Gaojun; Wang, Zhiqiang; Zhang, Qi; Yang, Yongfei; Ma, Wenjie (Frontiers in Earth Science, 2023)
When the sandstone reservoir enters the ultra-high water cut stage, the oil phase changes from continuous phase to discontinuous phase, which brings difficulties to the further development and utilization of the reservoir.In this paper, samples from sandstone reservoirs were selected, digital cores were accurately divided into the oil phase, water phase and particles were constructed based on three-dimensional CT scanning technology, and the discontinuous oil phase distribution law was studied. We use digital cores to construct pore network model and calculate pore radius, throat radius, pore-throat ratio, coordination number and tortuosity to study the influence of pore structure on discontinuous oil phase flow law. A micro-displacement experiment consisting of two phases of simulated reservoir formation and simulated reservoir development was designed. To improve the accuracy of the experiment, the related pressure is controlled to form bound water in the simulated reservoir formation stage. And in the simulated reservoir development phase, in-situ scanning of cores at different displacement stages was performed to obtain oil and water distribution at different stages in the same location. The number of oil droplets, 3D shape factor, Euler number and saturation coefficient of oil phase were calculated, and the micro-remaining oil clumps were quantitatively analyzed. According to the morphology and distribution characteristics, the remaining oil of discontinuous phase is divided into the throat, the film, the droplet, the island and the corner.